a. Eliminate any fractions by multiplication.

b. Simplify each side of the equation as much as possible by combining like

terms.

c. Use the addition property to simplify the equation so that all terms with the

desired variable are on one side of the equation and all numbers and variables other

than the one being solved for are on the other side.

d. Use multiplication or division to get an equation with just the desired variable

on one side.

e. Check your answer by substituting the solution back into the original equation

and evaluating it for truth when practical.

a. Solve for x:

3[1 - 2(x + 1)] = 2 - x

3[1 - 2x - 2] = 2 - x

simplify

3(-1 - 2x) = 2 - x

-3 - 6x = 2 - x

-3 - 5x = 2

add x to both sides

-5x = 5

add 3 to both sides

x = -1

divide both sides by -5

Check the Solution.

3[1 - 2(-1 + 1)] = 2 - (-1)

substitute -1 for all x

3[1 - 2(0)] = 2 - (-1)

evaluate

3(1) = 2 + 1

true

3=3

MD0837

1-10